2021
DOI: 10.3390/v13071237
|View full text |Cite
|
Sign up to set email alerts
|

Case Study of Two Post Vaccination SARS-CoV-2 Infections with P1 Variants in CoronaVac Vaccinees in Brazil

Abstract: The rapid development of efficacious and safe vaccines against coronavirus disease 2019 (COVID-19) has been instrumental in mitigating the transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Moreover, the emergence of SARS-CoV-2 variants raised concerns on the efficacy of these vaccines. Herein, we report two cases of breakthrough infections with the P1 variant in patients vaccinated with CoronaVac, which is one of the two vaccines authorized for emergency use in the Brazilian immuniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…After mRNA vaccine administration such as Pfizer or Moderna (mRNA-1273, Moderna, Cambridge, MA, USA), breakthrough confirmed cases were reported worldwide, mainly caused by VOCs such as Alpha B.1.1.7 [20][21][22][23] and Beta B.1.351 [21,24], in Israel [20,21], Greece [22], Germany [24], and Belgium [23]. The P1 (Gamma VOC) variant was reported in patients with CoronaVac from Brazil [25]. In the USA, a predominance of B.1.526 (Iota VOI) or B.1.1.7 (Alpha VOC) occurred in breakthrough infections in New York [26,27], Massachusetts [28], and other parts of the country [29].…”
Section: Discussionmentioning
confidence: 99%
“…After mRNA vaccine administration such as Pfizer or Moderna (mRNA-1273, Moderna, Cambridge, MA, USA), breakthrough confirmed cases were reported worldwide, mainly caused by VOCs such as Alpha B.1.1.7 [20][21][22][23] and Beta B.1.351 [21,24], in Israel [20,21], Greece [22], Germany [24], and Belgium [23]. The P1 (Gamma VOC) variant was reported in patients with CoronaVac from Brazil [25]. In the USA, a predominance of B.1.526 (Iota VOI) or B.1.1.7 (Alpha VOC) occurred in breakthrough infections in New York [26,27], Massachusetts [28], and other parts of the country [29].…”
Section: Discussionmentioning
confidence: 99%
“…Although the information presented here must be interpreted with caution because the sample size is small to generalize, some strengths of our study are worth noting, such as the serial testing after vaccination and infection and the measurement of T-cell responses in addition to humoral response. Previous reports have been focused on viral sequence information or antibodies detection on samples obtained after the onset of symptoms (11,12,39,42,43). This new information could be the interest to the scientific community and health authorities due to the urgent need to understand the individual variables that predispose to breakthrough infections and further find a correlate of protection that has not been established to date for SARS-CoV-2 infections; yet, some studies suggest that the level of neutralizing antibody titers is highly predictive of immune protection (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…The seropositive response was more frequent in females than males, and persons aged between 18–59 years presented with a higher frequency of humoral immunity. A case study in Brazil suggested that CoronaVac reduces the severity of illness after infection by P.1 variant of SARS-CoV-2, however, the argument may be raised on the sample size (2) being too small [ 168 ]. Single-dose of CoronaVac to seropositive persons with a history of COVID-19 infection produced more antibodies than a double-dose of vaccine to seronegative individuals in Indonesia [ 169 ].…”
Section: Vaccines Approved For Public Usementioning
confidence: 99%